An Information Model for Humanitarian Management in Thai Supply Chain - Artaphon Chansamut (ExcelingTech, 2023)
This study aim to develop an information model for humanitarian management in Thai supply chain and to assess an information model for humanitarian management in Thai supply chain. The research methodology was divided into three step namely synthesize former researches relevant to the elements an information model for humanitarian management model in Thai supply chain and developing the examined in terms of its quality by ten expert include data were analysed by mean, standard deviation .The research found there were six type of an information model for humanitarian management in Thai supply chain namely Main element ,Donors, Beneficiaries, Suppliers , Humanitarian organizations and Customers. The results from experts have evaluated an information model for humanitarian management in Thai supply chain is high level of appropriateness and can be appropriately applied in actual work settings.